Effects of Garlic (Allium sativum) feed supplement on Hemato-Biochemical properties in broiler chickens with sub-clinical toxicity of lead (Research in Agriculture Livestock and Fisheries, 2015)
The present study was conducted to estimate the garlic feed supplement on hematobiochemical parameters in lead exposed broiler chickens. 350 commercial broiler chickens were grouped into five, as T0, T1, T2, T3 and T4 consisting of 70 birds each, where T0 served as control. T1 was provided with lead acetate @ 100mg/kg body weight, T2 @ 100mg/kg lead acetate + 1% garlic supplement, T3 was fed @ 100mg/kg lead acetate + 2% garlic supplement and T4 @ 100mg/kg lead acetate + 4% garlic supplement .It was observed that Garlic supplementation in feed has got some ability to maintain normal values of erythrocytes, leukocytes, ALT, AST & Cholesterol parameters in spite of treatment with lead acetate. It was also found highly significant (P